2022
DOI: 10.1021/acs.est.1c06831
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic Cultivation of Microalgae Using Biogas as the Substrate

Abstract: Biogas utilization through biotechnology represents a potential and novel technology. We propose the microalgal mixotrophic cultivation to convert biogas to microalgae-based biodiesel, in which methanotroph was co-cultured to convert CH4 to organic intermediate (and CO2) for microalgal mixotrophic growth. This study constructed a co-culture of Methylocystis bryophila (methanotroph) and Scenedesmus obliquus (microalgae) with biogas feeding. Compared with the single culture of S. obliquus, higher microalgal biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Some processes that undergo a thermochemical transformation include gasification (syngas production), thermal liquefaction (bio-oil production), pyrolysis (bio-oil, syngas, charcoal production, etc. ), and direct burning or combustion (heat and electricity generation). , The biochemical reaction illustrates the natural bioprocessing of biomass to produce biofuels. Anaerobic digestion (biogas generation), alcoholic fermentation (bioethanol production), and photobiological hydrogen production are all examples of biochemical transformations (production of biohydrogen) .…”
Section: Microalgae As An Efficient Model For Capturing Carbon and Pr...mentioning
confidence: 99%
“…Some processes that undergo a thermochemical transformation include gasification (syngas production), thermal liquefaction (bio-oil production), pyrolysis (bio-oil, syngas, charcoal production, etc. ), and direct burning or combustion (heat and electricity generation). , The biochemical reaction illustrates the natural bioprocessing of biomass to produce biofuels. Anaerobic digestion (biogas generation), alcoholic fermentation (bioethanol production), and photobiological hydrogen production are all examples of biochemical transformations (production of biohydrogen) .…”
Section: Microalgae As An Efficient Model For Capturing Carbon and Pr...mentioning
confidence: 99%
“…al., [15] have employed microalgae for simultaneous biogas upgrading and nutrient removal from a digester centrate in an outdoor high-rate algal pond. Also, it was reported that compared with air sparing, biogas sparging could significantly increase biomass productivity because of high CO2 availability [16]. The atmospheric level of CO2 is very low (0.0387% (v/v)) and is insufficient to achieve a high rate microalgal biorefinery [17].…”
Section: Introductionmentioning
confidence: 99%
“…Under carbon supplementation, the ammonium assimilation is increased leading to reduced ammonium toxicity. Moreover, mixotrophic cultivation with ammonium could greatly enhance microalgal growth, biomass, total lipid, and particularly TAG content [13,14].…”
Section: Introductionmentioning
confidence: 99%